2019
DOI: 10.1111/jbi.13780
|View full text |Cite
|
Sign up to set email alerts
|

Combining correlative and mechanistic niche models with human activity data to elucidate the invasive potential of a sub‐Antarctic insect

Abstract: Aim Correlative species distribution models (SDMs) are subject to substantial spatio‐temporal limitations when historical occurrence records of data‐poor species provide incomplete and outdated information for niche modelling. Complementary mechanistic modelling techniques can, therefore, offer a valuable contribution to underpin more physiologically informed predictions of biological invasions, the risk of which is often exacerbated by climate change. In this study we integrate physiological and human pressur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 67 publications
0
29
0
1
Order By: Relevance
“…With the species already having a wide distribution in parts of the archipelago, knowledge of its past and current distribution provide valuable insight into the environmental drivers of its geographic spread, and help identify suitable habitats vulnerable to colonisation by the species. This body of knowledge, which could serve for making predictions on future geographic expansion 104 , underpins the current urgent requirement to define and implement effective biosecurity measures (i.e. detailed inspection and cleaning of clothing, footwear, equipment, freight, vehicles and vessels) in concert with the management of the National Nature Reserve, in particular when visiting sites not yet colonized by M. soledadinus.…”
Section: Discussionmentioning
confidence: 99%
“…With the species already having a wide distribution in parts of the archipelago, knowledge of its past and current distribution provide valuable insight into the environmental drivers of its geographic spread, and help identify suitable habitats vulnerable to colonisation by the species. This body of knowledge, which could serve for making predictions on future geographic expansion 104 , underpins the current urgent requirement to define and implement effective biosecurity measures (i.e. detailed inspection and cleaning of clothing, footwear, equipment, freight, vehicles and vessels) in concert with the management of the National Nature Reserve, in particular when visiting sites not yet colonized by M. soledadinus.…”
Section: Discussionmentioning
confidence: 99%
“…The data presented lay the foundation for future studies of this unusual insect’s distribution, ecology, phenology, physiology and general biology. With improved knowledge of the species’ preferred microhabitats, we are better able to predict other locations where it may occur, and even to extrapolate the risk of it being transported elsewhere (e.g., in species distribution modelling, which can involve the direct use of GIS data or a combination of biogeographical, physiological and meteorological data [ 33 , 60 , 61 , 62 ]).…”
Section: Discussionmentioning
confidence: 99%
“…This group includes Belgica antarctica Jacobs (1900), endemic to the Antarctic Peninsula and South Shetland Islands [ 24 , 25 , 26 ], and Eretmoptera murphyi Schaeffer (1914), originally described from and endemic to sub-Antarctic South Georgia and now introduced to the maritime Antarctic Signy Island [ 27 , 28 , 29 , 30 , 31 ]. Everatt et al [ 32 ] concluded that the latter species was pre-adapted to harsher conditions than what currently prevail in its native South Georgia, where it is now known to be palaeoendemic [ 24 , 25 ] and, therefore, has the potential to invade the Antarctic Peninsula region [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the presence of balanomorph barnacles and live individuals of the cosmopolitan pelagic barnacle, Conchoderma auritum, demonstrated the potential for non-native species to be transported to Antarctica this way (Hughes and Ashton 2017). Increasingly, modeling approaches are being used to predict potentially wide ranging future changes in distribution of both native and non-native terrestrial species in Antarctica (Bartlett et al 2020;Contador et al 2020;Hughes et al 2019;Pertierra et al 2017Pertierra et al , 2020.…”
Section: Biological Invasionsmentioning
confidence: 99%